The Effective Equation of Motion on the Brane World Gravity - F. P. Zen; B. E. Gunara; H. Zainuddin (Institute for Research and Community Services (LPPM) ITB, 2006)
Randall-Sundrum single brane system (RS II) is investigated systematically, with an emphasis of the effective equation of motion on the brane, by using a low energy expansion method (gradient expansion method) in the bulk. Through the junction condition, we deduce in the zeroth order fine tuning for RS model. The modified Einstein equation, as well as Friedmann equation with dark energy radiation on the brane is derived from the first order expansion. We also clarify the emergence of the AdS/CFT correspondence for the case of the higher order expansion in a low energy iteration scheme.